1989
DOI: 10.1136/gut.30.2.161
|View full text |Cite
|
Sign up to set email alerts
|

Duodenal and antral mucosal prostaglandin E2 synthesis in a study of normal subjects and all stages of duodenal ulcer disease treated by H2 receptor antagonists.

Abstract: Group (cl) ulcer rim made 49-8 (22.7) and at all stages ulcer rim and scar made less than the control duodenal bulb (p<002). Uninvolved duodenal bulb from groups (cl) (63-4 (31i0)), (c2) (83-6 (38 5)), and (c3) (81-5 (31-1)), however, also made significantly less than controls (p<002) and a similar though non-significant trend was seen in group (c4). Biopsies from the second part of the duodenum did not synthesise significantly less than the control group but a similar trend was noticed at each stage of ulcer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1990
1990
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Prostaglandin (PG) E 2 synthesis was measured by using a radioimmunoassay (anti‐PGE 2 antibody; Sigma Chemicals, St Louis, MO, USA) by following the method described by Pugh et al 17 …”
Section: Resultsmentioning
confidence: 99%
“…Prostaglandin (PG) E 2 synthesis was measured by using a radioimmunoassay (anti‐PGE 2 antibody; Sigma Chemicals, St Louis, MO, USA) by following the method described by Pugh et al 17 …”
Section: Resultsmentioning
confidence: 99%
“…Relative deficiency of PGEz synthesis has been suggested, using methods of tissue culture (22,23) and controlled trauma (21). Other studies (29,30), however, have not demonstrated changes in PGE,?…”
Section: Discuss I 0 Nmentioning
confidence: 98%
“…Studies examining mucosal levels of prostaglandin (19,20) are therefore difficult to interpret, since the majority measured will have been formed during processing. Reservations also apply to studies in which standardized trauma is used (2,21), since this may be difficult to achieve, and other variables are introduced, such as availability of cofactors. Studies of prostaglandin synthesis by cell cultures (22) or mucosal homogenates (24) suffer from the drawback that simultaneous degradation capacity is not measured.…”
Section: Discuss I 0 Nmentioning
confidence: 99%
“…In two published studies, there was good reproducibility in PG levels when multiple biopsies were homogenized and assayed repeatedly. But wide variation occurred in prostaglandin levels when assayed separately, suggestive of biological rather than methodological variation [41,42]. Should we measure endogenous prostglandins or in vitro synthesis of prostaglandins?…”
Section: Development Of Prostaglandins (Pgs) As Potential Sebs Of Drumentioning
confidence: 99%
“…Should we measure endogenous prostglandins or in vitro synthesis of prostaglandins? Several different assay methods are available, including measurement of exogenous synthesis of PGs, as in ex vivo culture of colonic biopsies incubated with [ 14 C] arachidonic acid and measurement of radiolabelled products [43,44]; and measurement of endogenous synthesis of PGs, by snap-freezing freshly obtained minimally manipulated tissue, assaying it within an hour of procurement [42,45], and either adding indomethacin to the snap-frozen tissue [41] or homogenizing it at 0°C before incubation at high temperature to stop PG production [45]. Assay recovery may vary with extraction techniques (formic acid/radioimmunoassay method [41] vs. chloroform extraction and gas chromatographymass spectroscopy method [46]).…”
Section: Development Of Prostaglandins (Pgs) As Potential Sebs Of Drumentioning
confidence: 99%